(3eNJda GdTjYI aj CMcGe GdTQjYIs - (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfi deG hbaJ Ydi cJH CUMGHfG GdeJbOejf hLOJ Hjfge NdGakG ai eSGFd cKjQI s
(3BNQgG (B:s
(3hGdJMbjb Cf Jbhd aGf NQL Edi YQaI dbVGA GdfSc s
(3GdfSNI HgG MhGTs
(3Hg WeSs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3abg GdePGgH GdCNQis